Enhanced delineation of glacial clastic reservoirs by the application of petroelastic well correlation and seismic inversion: Case study - Alansari, A. (Slovnaft VURUP a.s, 2018)
The Murzuq Basin is an intracratonic basin located in the South and Southwest (SW) Libya. Glacial Ordovician sandstones are the primary reservoir. However, identifying the top of the upper Ordovician reservoir and the interpretation of intra-Ordovician sequence directly from seismic using conventional methods are well-known challenges in the exploration and production of Murzuq basin. Even with the advent of 3D seismic and dense well database. Therefore, a detailed seismic and well data analysis of the study area was carried out. Sand-shale elastic baseline cut-offs and Vp and Vs cross-over were incorporated into the petro-elastic wireline interpretation. Also, post-stack seismic inversion was applied to generate elastic attributes (acoustic impedance and modelled VpVs). Vp and Vs cross-over successfully outlined the sand cycles when the Vp is located on the right side of the track, whereas the appearance of Vp on the left side indicates the presence of shale units. Seismic inversion provided a better lateral continuity and vertical top and inter reservoir events separation, which has improved their traceability. The VpVs attribute illuminated the reservoir area by the low percentage ratios of 1.6 and 1.8, which is the expected range for sand bodies with emphasis to their upper, mid and lower contacts. Hence, elastic properties derived from both wells and seismic enhanced the delineation of the top of the Upper Ordovician unconformity unit of Mamuniyat Formation (top reservoir) and enabled clear distinction between a non-reservoir unit of upper Ordovician formation (Bir-Tlaksin) and the primary reservoir. Â© 2018 Slovnaft VURUP a.s.